Meningkatkan Keterampilan Memecahkan Masalah Matematika Menggunakan Kombinasi Model PBL, NHT, dan Permainan ULTRASI - Nor Hafizah; Wahdah Refia Rafianti (GLOBAL SCIENTS PUBLISHER, 2025)
The selection of suitable instructional models significantly contributes to raising the quality of learning interactions between teachers and students. The present classroom-based action research was implemented with fifth-grade students at SDN Kertak Hanyar 1–3, Banjar Regency, to evaluate the impact of implementing Problem-Based Learning, Numbered Heads Together, and the ULTRASI game on learning activities, problem-solving skill, and mathematics achievement in the topic of